Optimizing Research Grants: Leveraging Technology and UAT for Enhanced Data Management - Jusoh, Zurina; Kadir, Harlinawati Abdul; Murad, Roslinda; Ahmad , Aslimariah (Journal of Ecohumanism, 2025)
The rapid evolution of technology continues to shape various aspects of our daily lives, offering innovative solutions to complex human challenges. As technology becomes more widely accepted, users often gain new experiences and adopt approaches that better suit their evolving needs. At Universiti Poly-Tech Malaysia (UPTM), lecturers are awarded research grants biannually to fund projects to foster experimentation and develop new tools. However, managing these grants can be challenging due to the need for accurate data handling, budgeting, and secure storage of sensitive information. An effective management system is crucial to ensure that data remains safe and accessible only to authorized users. A Research Management System (RMS) was developed using a web-based framework and Firebase Real-Time Database to address these challenges. The system, designed to centralize essential functions, including storing information on principal investigators, co-investigators, fund accounts, and essential documents, has significantly improved the management of research grants for lecturers. The success of the RMS can be attributed to the Agile Software Development Model, a methodology that played a crucial role in expediting development and ensuring flexibility. This paper focuses on the User Acceptance Testing (UAT) phase of the RMS, a critical step in software verification and validation. The UAT process ensures that the system meets user expectations, functions as intended, and addresses all previously identified issues. Implementing this system has streamlined the overall workflow and enhanced the experience of managing research grants for the lecturers.